In the Mean Time : Temporal Colonization and the Mexican American Literary Tradition - Murrah-Mandril, Erin (Book collections on Project MUSE., 2020)
"Taking a cue from Latina/o and borderlands spatial theories, "In the Mean Time" argues that time, like space, is a socially constructed, ideologically charged medium of power in the Southwest"--